Fließend - Schulze, Mario; Waltenspül, Sarine (Konstanz University Press, 2026)
In what formats does science become effective? In addition to books, articles and lectures, numerous films have also shaped its history. Fließend is a surprising and enlightening attempt to write a history of science, media and film in the 20th century based on a single film. Scientific moving images make up a considerable part of the analogue and digital film heritage. However, little is usually known about their production, distribution and reuse. The fluid dynamics film Entstehung von Wirbeln bei in Wasser bewegten Körpern (The Formation of Vortices in Bodies Moving in Water) was produced in Göttingen in the 1920s by Ludwig Prandtl. The book tells its story from the early 20th century to the present day as one of the desires in science, technology and art: for a valid image of flow phenomena, for applause in conference halls and cinemas, for evidence, aesthetics and legacy. This film provided a visual justification for boundary layer theory, contributed to the Gleichschaltung (enforced conformity) under National Socialism and fascinated the military-industrial avant-garde. It changed its epistemic functions and media formats just as it transcended institutions, national borders and political systems. The knowledge conveyed by the film contributed to the exploration of the depths of the oceans and the conquest of the heights of the skies, all the way to outer space. This knowledge has lost none of its fatal impact in times of global armament.